2019
DOI: 10.1002/wer.1045
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cd and Ni from water by graphene oxide and graphene oxide–almond shell composite

Abstract: The present study describes the preparation and capability of the graphene oxide/almond shell (GO@AS) composite by a freeze-drying method. The composite showed excellent ability to uptake nickel and cadmium ions, which were characterized by Fourier transform infrared spectrum and scanning electron microscopy techniques.The optimized values of pH, contact time, and adsorbent doses were found to be 7.5, 30-180 min, and 0.1 g, respectively. Also, adsorption isotherms of metal ions on adsorbents were determined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…15 Similarly, the adsorption ability of graphene oxide towards Cd(II) and Ni(II) was found to be greatly improved as it was incorporated with almond shell (graphene oxide/ almond shell composite) by a freeze-drying method. 16 However, it is worth noting that a complex assembly or synthesis process is generally needed for the preparation of desirable carbon nanomaterials-contained composites, which hence brought a large amount of wastage and cost as well as extra wastes. Interestingly, various carbon nanomaterialscontained composites being considered as by-products or industrial wastes are inevitably and largely being produced in daily industrial production, such as catalytic pyrolysis or reforming-involved industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Similarly, the adsorption ability of graphene oxide towards Cd(II) and Ni(II) was found to be greatly improved as it was incorporated with almond shell (graphene oxide/ almond shell composite) by a freeze-drying method. 16 However, it is worth noting that a complex assembly or synthesis process is generally needed for the preparation of desirable carbon nanomaterials-contained composites, which hence brought a large amount of wastage and cost as well as extra wastes. Interestingly, various carbon nanomaterialscontained composites being considered as by-products or industrial wastes are inevitably and largely being produced in daily industrial production, such as catalytic pyrolysis or reforming-involved industries.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Similarly, the adsorption ability of graphene oxide towards Cd( ii ) and Ni( ii ) was found to be greatly improved as it was incorporated with almond shell (graphene oxide/almond shell composite) by a freeze-drying method. 16 …”
Section: Introductionmentioning
confidence: 99%
“…After Ni(II) adsorption, they shifted to 3412, 1584, 1433, 990, 920, 561, and 525 cm -1 , while after Cd(II) adsorption, they were observed at 3385, 1603, 1435, 1013, 930, 570, and 534 cm -1 . The peak shifts to the lower frequencies indicate that the formation of composite bonds with Ni(II) and Cd(II) requires less energy for vibration [33].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…17 In the study of Yari Moghaddam et al, graphene oxide/almond shell composite fabricated by a freeze-drying method showed more effectiveness than a pure graphene oxide in the removal of cadmium (II) and nickel(II). 18 Nevertheless, a complex synthesis process is often needed for the preparation of an ideal carbon composite, which produces many by-products and requires additional costs.…”
Section: Introductionmentioning
confidence: 99%